Generative Artificial Intelligence in Islamic Religious Education: Opportunities, Ethical Challenges, and Pedagogical Transformation - Ainul Jaria Maidin; Ihsan Yilmaz; Esraa Al-Sarray (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The emergence of Generative Artificial Intelligence (GenAI) has significantly transformed educational practices by enabling personalized learning, automated content generation, and intelligent tutoring systems. Despite its growing adoption, limited research has examined its pedagogical implications within Islamic Religious Education (IRE). This study aims to analyze the opportunities, ethical challenges, and educational impacts of integrating GenAI into Islamic Religious Education. A qualitative research approach employing a systematic literature review and expert interviews was conducted. Data were analyzed using thematic analysis to identify key trends in AI-assisted Islamic learning. The findings indicate that GenAI enhances personalized instruction, supports adaptive learning, facilitates lesson planning, and improves students’ engagement with Islamic learning materials. However, ethical concerns—including academic integrity, algorithmic bias, misinformation, and excessive technological dependence—necessitate comprehensive ethical guidelines grounded in Islamic values. The study proposes an Islamic AI governance framework emphasizing transparency, accountability, digital ethics, and responsible AI use. The novelty of this research lies in developing an Islamic Generative AI Pedagogical Framework that integrates technological innovation with Islamic educational philosophy, providing practical guidance for responsible AI implementation in twenty-first-century Islamic education.